Recommendations for vaccination against ROTAvirus in PREMature newborns (ROTAPREM) - Javier Álvarez Aldeán; Susana Ares Segura; Celia Díaz González; Abián Montesdeoca Melián; Rubén García Sánchez; Héctor Boix Alonso; David Moreno-Pérez (Elsevier, 2019)
Rotavirus (RV) is the leading cause of severe acute gastroenteritis in infants worldwide. Most children are infected by RV by the age of 5 years, and especially in the first 2 years. Two oral attenuated vaccines against RV are licensed in industrialised countries, which have proven to be safe and effective against the disease.The main objective of these vaccines has been to reproduce the natural history of infection and protect against severe disease in the first months of life. Preterm infants are at higher risk of severe RV infection compared to full-term infants and infants with normal birth weight.Data collected on RV vaccination in preterm infants demonstrated that RV vaccines are effective and safe, compared with full-term infants, with a marginal risk of horizontal viral transmission and dissemination when vaccination is performed during hospitalisation.Preterm infants frequently require admission to hospital after the beginning of the 12th week of life, which suggests that they should receive RV vaccines during admission according to the official immunisation schedule. Resumen: El rotavirus (RV) es la causa principal de diarrea infantil grave en todo el mundo e infecta prácticamente a todos los niños en los primeros 5 años de vida, sobre todo en los primeros 2 años. Existen dos vacunas atenuadas de administración oral frente al RV disponibles en nuestro medio que han demostrado ser seguras y eficaces frente a la enfermedad.El objetivo principal de estas vacunas ha sido reproducir la historia natural de la infección y proteger frente a la enfermedad grave en los primeros meses de vida. Los recién nacidos prematuros son especialmente vulnerables a la enfermedad por RV, no solo por tener más riesgo de adquirir la infección, sino también por sus complicaciones.La vacunación frente al RV en niños prematuros ha mostrado resultados de eficacia y seguridad similares a los comunicados en niños a término, y los datos existentes sugieren un riesgo bajo de diseminación e infección nosocomial cuando la vacunación se realiza durante la hospitalización.Dado que un porcentaje estimable de recién nacidos prematuros permanecen ingresados en las unidades neonatales más allá de las 12 semanas de vida, se considera que estos, siempre que su condición clínica lo permita, deben recibir la vacunación frente al RV sin retrasos, incluso durante la hospitalización si así fuese necesario.